1986
DOI: 10.1002/cyto.990070515
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry reveals a high degree of genomic size variation and mixoploidy in various strains of the acellular slime mold Physarum polycephalum

Abstract: High-resolution flow cytometry, using avian erythrocytes as an internal standard, was employed to study constitutive genome size variation of GX-phase nuclei of Physarurn polgcephalum strains during the macroplasmodial stage of their life cycle. Our results document a previously unknown extent of genome size variation and mixoploidy in this organism. The unimodal diploid strain Tu 291 displayed the largest genome of the strains tested; in contrast, the Colonia strain displayed only half of the Tu 291 G2-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Regular cycles of endomitosis followed by cycles of division occur in some unicellulars, for example Entamoeba , Pelomixa and Phreatamoeba (Afonkin, 1986), some red algae (Goff & Coleman, 1986), the brown alga Ectocarpus siliculosus (Mueller, 1967), and it is also possible in Radiolaria (Raikov, 1982), foraminiferans (Roettger et al. , 1989), dinoflagellates (Silva & Faust, 1995), Raphidophytes (Yamaguchi & Imai, 1994), Physarum polycephalum (Kubbies et al. , 1986), some pyrsonymphids and actinopods (Haig, 1993), and the charophyte alga Coleochaete scutata (Hopkins & McBride, 1976).…”
Section: Polyploidization – Depolyploidizationmentioning
confidence: 99%
“…Regular cycles of endomitosis followed by cycles of division occur in some unicellulars, for example Entamoeba , Pelomixa and Phreatamoeba (Afonkin, 1986), some red algae (Goff & Coleman, 1986), the brown alga Ectocarpus siliculosus (Mueller, 1967), and it is also possible in Radiolaria (Raikov, 1982), foraminiferans (Roettger et al. , 1989), dinoflagellates (Silva & Faust, 1995), Raphidophytes (Yamaguchi & Imai, 1994), Physarum polycephalum (Kubbies et al. , 1986), some pyrsonymphids and actinopods (Haig, 1993), and the charophyte alga Coleochaete scutata (Hopkins & McBride, 1976).…”
Section: Polyploidization – Depolyploidizationmentioning
confidence: 99%
“…The nuclei of Physarum plasmodia are naturally synchronized, providing us with the opportunity to quantify chaperone transcript levels at specific stages of the cell cycle. Physarum cell cycle consists of a 0.5 h mitosis, a 3 h S-phase and a 6 h G2-phase with no G1-phase [ 53 ]. We observed two main expression patterns for chaperones: (i) group 1 ( PpHSP90, PpNASP, PpASF1, PpCAF1A, PpCAF1B, PpCABIN1, PpMCM2, PpPolE3, PpSPT16, PpPob3 : in yellow on the left) with elevated mRNA levels in early S-phase and late G2 phase, (ii) group 2 ( PpCAF1C, PpUBN, PpSWC2, PpSET, PpNAP1L1, PpAPLF : in magenta on the left) with elevated mRNA levels in mid S-phase ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, analyses of published transcriptomes showed that these three genes were not expressed in the various tested stages of the life cycle ( 6 , 15 ). These discrepancies might be due to sequencing issues, spurious assembly or sequence variations between strains, although the TU291 strain was shown to have one of the largest Physarum genome size ( 68 ).…”
Section: Discussionmentioning
confidence: 99%